Respuesta :

Hence the value of the expression above are as listed below

f(6+4) = 25

f(6)+f(4) = 20

f(6-4) = 1

f(6)-f(4) = 6

f(6*4) = 67

f(6)*f(4) = 91

Functions and values

Given the expression below f(x) = 3x - 5

f(6+4) = f(10) =3(10) - 5

f(6+4) = 25

f(6) = 3(6) - 5

f(6) = 18 - 5 = 13

f(4) = 3(4) - 5

f(4) = 7

f(6)+f(4) = 13+7

f(6)+f(4) = 20

f(6-4) = f(2) =3(2) - 5

f(6-4) = 1

f(6) = 3(6) - 5

f(6) = 18 - 5 = 13

f(4) = 3(4) - 5

f(4) = 7

f(6)-f(4) = 13-7

f(6)-f(4) = 6

f(6*4) = f(24) =3(24) - 5

f(6*4) = 67

f(6) = 3(6) - 5

f(6) = 18 - 5 = 13

f(4) = 3(4) - 5

f(4) = 7

f(6)*f(4) = 13*7

f(6)*f(4) = 91

Learn more on function and values here: https://brainly.com/question/2284360

#SPJ1

ACCESS MORE